Reassessment of low- and intermediate-risk endometrial cancer reports by gynecological pathologists increases risk classification without impacting outcome. (November 2022) - Alves Pinto de Andrade, Diocésio; Duval da Silva, Vinicius; Baiocchi, Glauco; de Macedo Matsushita, Graziela; Alves de Lima, Marcos; Paula Carvalho, Jesus; Batista Sandre, Letícia; De Brot, Louise; Manuel Reis, Rui; dos Reis, Ricardo
Highlights: Gynecological tumors are the most discordant in pathologists' review reports. Pathological reports of endometrial cancer done by experts may contribute to treatment. Despite disagreements between pathologists' reports, there is no impact in outcomes. Abstract: Objectives: A lack of agreement is often observed in pathological reviews performed by specialized and general pathologists. Four histopathological variables influence the risk classification of endometrial cancer: histological type; histological grade; myometrial invasion; lymph-vascular space invasion (LVSI). This study aimed to evaluate if changes in the risk classification after a specialized pathological review of low- and intermediate-risk endometrial cancer (LIREC) samples may impact disease-free survival (DFS). Methods: A retrospective cohort of 195 patients diagnosed with LIREC at Barretos Cancer Hospital was obtained. Two gynecologic pathologists re-evaluated the pathological reports. Through the histology report reviewed, we could determine their new risk classification. The Kappa concordance score was used to verify the concordance between the general's and specialized pathologists' reports, and the new risk classification was correlated with the patients' DFS. Results: The final reports led to changes in the histological type, histological grade, myometrial invasion, and lymphovascular space invasion in 13.3 %, 62, 8%, 18.3 %, and 11.1 % of cases, respectively. The Kappa concordance score for all variables was less than 0.7. In 54 patients (30 %), the risk classification was modified (κ = 0.396), of which 30 (55.5 %) cases upstaged. There was no difference in DFS for patients who had an upstaging in their European Society of Medical Oncology modified classification compared to those who maintained their initial risk classification (86.7 % vs 88.0 %, p = 0.77). Conclusion: Despite the differences in the reports reassessed by expert gynecological pathologists and the change (30%) in patients' risk classification, there was no difference in their DFS.